DEEP BACK MASSAGE EFFECT ON LABOR PAIN REDUCTION FIRST STAGE ACTIVE PHASE AND THE OPENING SPEED OF DELIVERING MOTHER AT BPS DLANGGU PUBLIC HEALTH CENTER MOJOKERTO DISTRICT: Level of Pain, Deep Back Massage, Childbirth, Cervical Opening - Lestari, Indah; Yuniarti, Siswari (LPPM Universitas PGRI Adi Buana Surabaya, 2010)
The process of childbirth is a natural cycle in a woman. Similarly, the pain during childbirth. Pain occurs due to contraction during the process of opening and thinning of the cervix. Increasing the frequency and duration of the contractions more intense pain is felt especially in primigravida mothers. This study aims to analyze the influence of the Deep Back Massage to the decrease of labor pain when active phase and the speed of the opening in the mother giving birth in the working area of BPS Dlanggu Public Health Center Mojokerto district. The study was true experimental design